2004
DOI: 10.1007/s00270-003-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Impact of Aortic Stent-Grafting in Patients with a Horseshoe Kidney

Abstract: Aortic stent grafting may be an alternative to surgery for patients with an abdominal aortic aneurysm and coexistent horseshoe kidney but is not without difficulties. This study examines the renal consequences of aortic stent grafting in such patients. This is a retrospective review of patients with horseshoe kidney in whom aortic stent grafting was performed between December 1995 and August 2000. Follow-up occurred within the EUROSTAR protocol and included measurement of serum creatinine. Of 130 patients in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Slight but permanent impairment of renal function was recently reported in three of four patients with HSK, in whom one to four minor accessory renal arteries were excluded during stent-graft positioning. 16 Obviously, HSK with multiple or important renal arteries arising from the aortic neck, the aneurism sac, or the iliac arteries cannot benefi t from this type of procedure. Moreover, a case of fatal type II endoleak from an excluded accessory renal artery was reported, which prompted some surgeons to deliberately occlude the accessory renal artery with coil embolization before attempting AAA endoluminal repair.…”
Section: Discussionmentioning
confidence: 99%
“…Slight but permanent impairment of renal function was recently reported in three of four patients with HSK, in whom one to four minor accessory renal arteries were excluded during stent-graft positioning. 16 Obviously, HSK with multiple or important renal arteries arising from the aortic neck, the aneurism sac, or the iliac arteries cannot benefi t from this type of procedure. Moreover, a case of fatal type II endoleak from an excluded accessory renal artery was reported, which prompted some surgeons to deliberately occlude the accessory renal artery with coil embolization before attempting AAA endoluminal repair.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of patients with CFE and a third of patients with HK have other urogenital, gastrointestinal, cardiopulmonary, skeletal, or chromosomal anomalies [6,7]. The variations of vascular supply [8] could make kidney surgery [9], kidney transplants [10], or surgical [11] and endovascular procedures on the aorta [12] difficult. Thus, imaging is very important, but a systematic analysis of the findings of all methods, especially of spiral CT, in conjunction with the relevant clinical data, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is not yet clear how many of these anomalous arteries and to what extent they can be safely covered. 7 Empirically, Jackson et al 6 suggested that an artery supplying up to 32% of the total parenchyma can be occluded in patients with normal renal function. Morphological evaluation with associated functional information can be done by a scintigraphic study that is able to give information about the parenchymal renal functional through capture and excretion of the radionucloide.…”
Section: Discussionmentioning
confidence: 99%
“…6 These features would determine lesions of the organ, which do not influence its function. 2 It is not yet clear how many of these anomalous arteries and to what extent they can be safely covered.…”
Section: Discussionmentioning
confidence: 99%